PENERAPAN MODEL PEMBELAJARAN ARGUMENT DRIVEN INQUIRY (ADI) UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN TERMOKIMIA DI KELAS XI MIA MAN 3 PEKANBARU - Pratiwi, Indah; Haryati, Sri; Azmi, Johni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The research about the Argument Driven Inquiry (ADI), model has been conducted in MAN 3 Pekanbaru. The purpose of this research is to determine wheterthe application of ADI learning can improve achievement and the influence of application of ADI learning model in class XI MIA MAN 3 Pekanbaru on the subject improve category N-Gain, Research on the application of learning model ADI has been done to improve student’s achievement on the subject of thermochemistry. Form of research is experiment research with pretest-posttest design. The sample consisted of two classes, XI MIA 2 class as experiment and XI MIA 1 class as control that randomly selected after testing normality and homogeneity. Experiment class was treated with implementing learning model ADI and the control class was treated conventional method. Analysis of data used t-test. Data of research obtained tcount > ttable (2,238> 1,673). It means that using learning model ADI can improve student’s achievement on the subject of thermochemistry in class XI of MAN 3 Pekanbaru. The category improvement of student’s achievement in experiment class was high category (N-Gain =0,86) and in control class was medium category (N-Gain =0,68).  Key Words:  Inquiry learning, Argument Driven Inquiry (ADI), Learning  Achievement,                     Thermochemistry